Spectroscopic Study of Copper Plasma Produced by Fundamental Nd: YAG Laser by LIBS (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2023)
Background:    The effect of laser wavelength on the analytical results obtained from LIBS by Nd: YAG laser diagnostics to copper element is experimentally investigated by Nd: YAG laser at 1064 nm wavelength. The temperature and density of electrons in copper plasma are calculated under (LTE) conditions.Materials and Methods:Various copper transitions were obtained. Identification of transition lines from the spectrum is carried out by comparing spectral lines with NIST atomic database. The results after performing the analysis were compared with (NIST) database.Results: The result showed that the various wavelengths obtained from the copper target tare with significant compatibility with the same wavelengths from the National Institute of Standards and Technology (NIST).Conclusion: LIBS technique proved to be a precise and accurate tool for calculating electron temperature and electron number density, the presence of different elements with very low tolerance, and diagnosing their concentrations.